Local-global policy in the context of an environmental crisis: proposition of a systemic analyse of environmental management. - Céline Ohresser; Élodie Piquette; Nathalie Gartiser (European Regional Science Association (ERSA), 2010)
Combining local and global policy on a cross bordered territory demands the building of a procedure. This is even more required in the case of environmental issues involving various actors who have to accept a common system of reference which guides the management of common natural ressource respecting ecological-friendly rules of the uses. Considering the environmental ethics as an emerging quality of an anthropo-ecological system, this article aims to interpret the reorganization of what the autors named as ' rhine river system' in the context of an ecological crisis (Liu J., et AL., 2007). It acts thus as a mediation between the riverside States to guide the actions in the sense of water protection,. It also reinforces the cooperation of the different states involved in its management (global level) as well as the riverside regions (local level). The main purpose of this procedure is the acceptance by the actors of a systemic perception of the Rhine. This acceptance is conditioned by the ability of every use to open to that perception. According to us, this procedure can be analysed as the emergence of a common ecological ethics implemented in a cross bordered region. In this way, we suggest three hypothesis : Confronted to a crisis, the environmental ethics appears as an emergent quality of the Rhine river's system. The Rhine anthropo-ecological system is composed of sub-systems; each one communicates and exchanges informations only in the context of risk. Ethics plays a role of metasystem, transcending the self referential systems. Through the meeting of two disciplines (sociology and conception), is suggested in order to explain the organization of communication and information's process between the various and self-referential systems. The main purpose of this communication is to focus on the action of each system in conditioning at last the dessimination and the acceptance of an unique environmental ethics, understood as the recognition of the intrinsic properties of the Rhine river ecosystem, and adapted to the references of each system involved.
Keywords: 330; System (ecosystem; multi agent system; hydrosystem); self referential subsystem; Procedure and concept of action